Kecakapan Subjek Hukum Lanjut Usia Penderita Demensia - Andika Putra Eskanugraha (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2021)
ABSTRACT: People as legal subjects must be protected as holders of rights and responsibilities. The protection is provided by the state within the framework of statutory regulations as a product of the state law. The state should bear legal certainty in regulating a person's ability to act legally. This arrangement is essential considering the minimum age limit and the provisions or requirements for being proven to be legally competent. The age requirement within the minimum limit determined by a statutory regulation varies broadly. The diversity of age thresholds has led to several critics and suggestions within the academic community for a uniformity of legislation. The maximum limit of a person's proficiency has never been discussed in a statutory regulation. This maximum limitation is very vital considering that humans who have lived for a long time, are confirmed to have physical limitations and mostly affect their ability particularly in law. The ability of a person is going to have a deficiency once getting older. There is no limit to the maximum age of proficiency, which creates many legal problems that can arise in the community. This is because someone has dementia and other people do not know it apart from family members. The agreement made by a person experiencing dementia affects the person concerned specifically in article 1320 point 2 Burgerlijk Wetboek. Aging problems, which cause dementia, can be addressed by the government in terms of a person's ability, limitation can be made in a statutory regulation as a form of protection. KEYWORDS: Ability, Legal Subjects, Dementia.